The Effects of Elevating the Supplemental Poverty Measure on Government Program Eligibility and Spending - Kevin Corinth (American Enterprise Institute (AEI), 2023)
Without Congressional action, the recently released National Academy of Sciences report, "An Updated Measure of Poverty: (Re)Drawing the Line," could have substantial effects on government program eligibility and spending—if its recommendation to "redraw the line" is implemented by the Census Bureau, and the Supplemental Poverty Measure (SPM) is made the official one by the Office of Management and Budget. This change to the official poverty measure could be made as soon as September 2023, and major government transfer programs whose eligibility standards are tied to the official poverty guidelines could be affected in 2024. In this paper, I first project that making the SPM the official poverty measure would increase the poverty guideline for a family of four by 6,400 (20 percent) in 2024 and by 13,150 (34 percent) in 2033. I also show that if state-specific SPM thresholds were used, then poverty guidelines would be higher in high-cost states like California (21 percent higher than the national average) and lower in low-cost states like West Virginia (19 percent lower than the national average). I then estimate how the change in the poverty guidelines would affect government spending on the two largest entitlement programs whose eligibility standards are tied to the official poverty guidelines. I estimate that over the next decade (2024-2033) Supplemental Nutrition Assistance Program spending would be 47 billion higher, and Medicaid spending would be 78 billion higher. Thus, basing the U.S. poverty guidelines on the SPM would increase government spending by at least 124 billion over the next decade.
Keywords: 330